Enhanching Student's reading Achievement by Applying CLE - Ranti Pertama Sari; Inda Lia; Kurnia Febianti (CV. Kalimasada Group Profesional, 2024)
This study aimed to describe CLE method in enchanching students' reading achievement through review experts' opinions and results of previous research on the definition and benefits of CLE. The finding of study show that, CLE was effective media, and the media that could enchanching students' writing achievement regarding their motivation, literacy, creativity, and critical thinking.CLE also can be used in developing students creativity in reading comprehend , especially to support students reading. The students should increase their knowledge about vocabulary, grammar, and another aspects of reading. The study was conducted as library research that relies on the results of previous studies and experts' opinions for answering the present study's research questions.